The Relationship between Learning Models and the Level of Knowledge of Basic Freestyle Swimming Techniques among Members of the Tirta Krisna Jembrana Swimming Club - Dewi, Komang Ayu Krisna; Budiman, Ali (STKIP Paasundan Press, 2024)
This research aims to determine the relationship between the learning model and the level of knowledge of basic freestyle swimming techniques among members of the Tirta Krisna Jembrana Swimming Club. Knowledge of basic freestyle swimming techniques is very important for beginner swimmers so they can master efficient and correct movements, and reduce the risk of injury. The learning model used in this research includes a conventional approach and a repetitive practice-based approach. This research uses quantitative methods with a correlational design to determine the relationship between variables. The sample used was 20 members of the Tirta Krisna Jembrana Swimming Club who were selected using purposive sampling. Data was collected using a questionnaire consisting of two parts, namely the learning model received and the level of knowledge of basic freestyle swimming techniques. The results of the analysis show that there is a significant positive relationship between the learning model and the level of knowledge of basic freestyle swimming techniques. This shows that implementing an appropriate learning model can increase members' understanding of basic freestyle swimming techniques. This research contributes to the development of more effective learning methods in improving swimming skills in swimming clubs, especially in the Jembrana area.